حوار الدّعوة بين التّأسيس والتّجديد: قراءة في الوسائل المستخدمة في ذلك: The Dialogue of Da‘wah between Tradition and Modernity: A Study about Its Sources - Maryam al-duwaihash (الدراسات الإسلامية, 2022)
This article discusses the classical and modern sources of da‘wah (preaching) such as dialogue, letters, and media vis-à-vis the related opinions of Muslim scholars. Dialogue is an important aspect of human life. Human beings have always used it in political, social and other relationships. It provides opportunities for solving problems amicably because it is easy to understand the views of the “other” through it. According to the teachings of the Qur’ān and the sunnah, dialogue plays an important role in inviting people to Islam. Its various styles have been mentioned in these primary sources. The Messenger of Allah (peace be on him) sent letters to various kings of his time and negotiated with foreign delegates. Since the world has become a global village in the present era and there has been tremendous progress in the modern means of communication, the use of modern means can play a fundamental role in preaching religion and people should be invited to religion by using these modern means. This article discusses the means of dialogue adopted in ancient and modern times. In the present era, the use of the Internet can prove to be a useful method of preaching Islam. Similarly, print and electronic media are also very important means of dialogue.